Residential surrounding greenness is associated with improved lung function in adults: a cross-sectional study in eastern China - Wenhao Zhang; Wenjia Peng; Jun Cai; Yuhong Jiang; Cheng Zhou; Zhenqiu Zha; Jing Mi (BMC, 2023)
Abstract Background While benefits of greenness exposure to health have been reported, findings specific to lung function are inconsistent. The purpose of this study is to assess the correlations of greenness exposure with multiple lung function indicators based on chronic obstructive pulmonary disease (COPD) monitoring database from multiple cities of Anhui province in China. Methods We assessed the greenness using the annual average of normalized difference vegetation index (NDVI) with a distance of 1000-meter buffer around each local community or village. Three types of lung function indicators were considered, namely indicators of obstructive ventilatory dysfunction (FVC, FEV1, FEV1/FVC, and FEV1/FEV3); an indicator of large-airway dysfunction (PEF); indicators of small-airway dysfunction (FEF25%, FEF50%, FEF75%, MMEF, FEV3, FEV6, and FEV3/FVC). Linear mixed effects model was used to analyze associations of greenness exposure with lung function through adjusting age, sex, educational level, occupation, residence, smoking status, history of tuberculosis, family history of lung disease, indoor air pollution, occupational exposure, PM2.5, and body mass index. Results A total of 2768 participants were recruited for the investigations. An interquartile range (IQR) increase in NDVI was associated with better FVC (153.33mL, 95%CI: 44.07mL, 262.59mL), FEV1 (109.09mL, 95%CI: 30.31mL, 187.88mL), FEV3 (138.04mL, 95%CI: 39.43mL, 236.65mL), FEV6 (145.42mL, 95%CI: 42.36mL, 248.47mL). However, there were no significant associations with PEF, FEF25%, FEF50%, FEF75%, MMEF, FEV1/FVC, FEV1/FEV6, FEV3/FVC. The stratified analysis displayed that an IQR increase in NDVI was related with improved lung function in less than 60 years, females, urban populations, nonsmokers, areas with medium concentrations of PM2.5 and individuals with BMI of less than 28 kg/m2. Sensitivity analyses based on another greenness indice (enhanced vegetation index, EVI) and annual maximum of NDVI remained consistent with the main analysis. Conclusions Our findings supported that exposure to greenness was strongly related with improved lung function.